Peran Madzhab Basrah dalam Pengembangan Ilmu Nahwu: Tinjauan pada Kitab al-Muyassar karya Aceng Zakaria - Abdurrohman, Roni; Sopian, Asep (Ukazh: Journal of Arabic Studies, 2023)
Kitab Al-Muyassar Fii 'Ilmi Al-Nahwi karya Aceng Zakaria memiliki kekhasan serta karakteristik yang kuat dalam konten materinya serta sering digunakan sebagai referensi dalam pembelajaran di beberapa universitas serta Pondok Pesantren. Serta madzhab-madzhab nahwu juga berperan dalam kitab Al-Muyassar Fii 'Ilmi Al-Nahwii, salah satunya ialah Madzhab Bashrah. Maka penelitian ini menginvestigasi peran Madzhab Bashrah dalam pengembangan ilmu Nahwu melalui kitab Al-Muyassar karya Aceng Zakaria. Penelitian ini menggunakan metode kualitatif studi kepustakaan. Temuan penelitian menunjukkan bahwa banyaknya penggunaan istilah madzhab Bashrah dalam kitab tersebut menunjukkan dominasi Madzhab Bashrah dalam isi kitab tersebut. Beberapa contoh penggunaan istilah tersebut antara lain: penggunaan istilah naib al-fail untuk menunjukkan kata benda yang menggantikan kedudukan pelaku, penggunaan istilah dzaraf serta maf’ul fiih untuk menunjukkan keterangan baik tempat maupunpun waktu, penggunaan istilah raf’u, nashbu, jarru, serta jazmu pada amil-amil I’rob, menurut pansertagan ulama Mazhab Bashrah, tanda-tanda isim terletak pada kemunculan alif serta lam, yang menjadi indikator penting dalam pengidentifikasian isim penggunaan istilah la nafiyah lil jinsi. The book "Al-Muyassar Fii 'Ilmi Al-Nahwi" by Aceng Zakaria possesses distinctiveness and strong characteristics in its content material, and it is frequently used as a reference in learning at several universities and Islamic boarding schools. Among the various schools of Arabic grammar (nahw), the Basrah School also plays a significant role in the book "Al-Muyassar Fii 'Ilmi Al-Nahwi" authored by Aceng Zakaria. Therefore, this research investigates the role of the Basrah School in the development of Nahw science through Aceng Zakaria's book "Al-Muyassar." This study employs a qualitative method of literature review. The research findings indicate that the extensive usage of Basrah School terminology in the book demonstrates the dominance of the Basrah School within its content. Several examples of such terminology usage include: (1) the use of the term "naib al-fail" to denote a noun that replaces the position of the doer, (2) the use of the terms "dzaraf" and "maf’ul fiih" to indicate both place and time specifications, (3) the use of the terms "raf’u," "nashbu," "jarru," and "jazmu" in the amil-amil I'rob, (4) according to the views of Basrah School scholars, the signs of isim (noun) are found in the occurrence of alif and lam, which serve as important indicators in identifying nouns, and (5) the use of the term "la nafiyah lil jinsi”.